Statistical Modeling and Characterization of Laser Marking on AISI 301LN Stainless Steel Using Short-Pulsed Fiber Laser - Mohammad Rezayat; Mojtaba Karamimoghadam; Nicola Contuzzi; Giuseppe Casalino; Antonio Mateo (Metals)
This study explores the effects of nanosecond short-pulsed fiber laser processing on AISI 301LN stainless steel, focusing on optimizing surface characteristics through precise parameter control. Using a Design of Experiments (DOE) approach combined with response surface methodology (RSM), the influence of laser power (30–60 W) and the number of laser passes (5–15 times) was systematically investigated. The results demonstrate that increasing the laser power and passes significantly affected the surface properties. The highest surface roughness of 16.8 µm and engraving width of 51 µm were achieved with 60 W power and 15 passes, whereas the lowest roughness of 13.8 µm and width of 35 µm were observed with 30 W power and 5 passes. Wettability measurements revealed an inverse correlation with roughness, with contact angles ranging from 86.4° for rougher surfaces to 92.4° for smoother textures. The findings demonstrate the capability of short-pulsed fiber laser processing to tailor surface properties effectively, with potential applications in manufacturing and surface engineering where controlled roughness and wettability are critical.